Análises térmicas em sistemas poliméricos: uma ferramenta para a avaliação da degradação - Lopes, Jameson Santos (Universidade Federal de São Carlos, 2024)
In the contemporary world, the demand for polymeric materials has grown intensely to meet the pace of consumption. In view of this, concern about the disposal of polymers becomes an issue when considering waste management. Thus, investigating the impact of degradation on the physical and chemical properties of these materials by means of thermal analyses is a possible approach to this problem. To accomplish this, this study was structured to introduce basic concepts on the subject as well as address the degradation mechanisms undergone by polymers and their precursor agents, refer to the impacts of degradation on the properties of some polymeric systems, and discuss the fundamentals, characteristics, and parameters of thermal analyses. Thermal analyses are a group of various techniques that measure the physical and chemical properties of a given material as a function of temperature under controlled atmospheric, heating and cooling conditions. The properties of the sample are analyzed by monitoring the changes in the material as a function of time and temperature compared to a reference, which makes it possible to determine certain physical and chemical properties of the material in order to determine its possible applications, storage, behavior, and transport. For this work, the focus will be on Differential Scanning Calorimetry (DSC) analyses, which monitor the flow of heat through the sample over time and temperature. With DSC it is possible to determine the Vitreous Transition Temperature (Tg), Crystaline Melting Temperature (Tm) and Crystallization Temperature (Tc), the melting enthalpy (∆Hf), degree of crystallinity (Xc), specific heat, phase transition, curing and crystallization kinetics. And Thermogravimetric Analysis (TGA), which relates the change in mass in a sample under a controlled atmosphere; it investigates the thermal decomposition profile of the material. With TGA, we can study the thermal stability of the sample, thermal decomposition, moisture content and pyrolysis of certain substances. This work will conclude with a discussion of two case studies. The first one will address the use of thermal analyses to understand the effects of degradation on Nylon 6,6, while the second will investigate the durability of cables in nuclear plants.
Thermal analysis of polymeric systems: a tool for assessing degradation
Keywords: Materiais; Polímeros; Análises térmicas; Degradação; Materials; Polymer; Thermal analysis; Degradation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES